Respuesta :
basically
1. replace f(x) with y
2. replace all y with x and all x with y
3. solve for y
4. replace y with f⁻¹(x)
so
f(x)=2x
replace
y=2x
switch
x=2y
divide both sides by 2
[tex] \frac{x}{2}=y [/tex]
[tex] y= \frac{x}{2} [/tex]
replace
[tex] f^{-1}(x)= \frac{x}{2} [/tex]
the answer is the 2nd one
1. replace f(x) with y
2. replace all y with x and all x with y
3. solve for y
4. replace y with f⁻¹(x)
so
f(x)=2x
replace
y=2x
switch
x=2y
divide both sides by 2
[tex] \frac{x}{2}=y [/tex]
[tex] y= \frac{x}{2} [/tex]
replace
[tex] f^{-1}(x)= \frac{x}{2} [/tex]
the answer is the 2nd one